46th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2010
DOI: 10.2514/6.2010-6541
|View full text |Cite
|
Sign up to set email alerts
|

A Historical Systems Study of Liquid Rocket Engine Throttling Capabilities

Abstract: This is a comprehensive systems study to examine and evaluate throttling capabilities of liquid rocket engines. The focus of this study is on engine components, and how the interactions of these components are considered for throttling applications. First, an assessment of space mission requirements is performed to determine what applications require engine throttling. A background on liquid rocket engine throttling is provided, along with the basic equations that are used to predict performance. Three engines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…3, 2018 ber pressure. 17,21) Under the condition of maximum throttle, when a pressure drop in the oxygen injector remains at 15%, it will drop further as throttling is reduced. This large pressure drop in injection affects the necessary pump power and operating range of the engines.…”
Section: à1=4 ð8þmentioning
confidence: 99%
See 1 more Smart Citation
“…3, 2018 ber pressure. 17,21) Under the condition of maximum throttle, when a pressure drop in the oxygen injector remains at 15%, it will drop further as throttling is reduced. This large pressure drop in injection affects the necessary pump power and operating range of the engines.…”
Section: à1=4 ð8þmentioning
confidence: 99%
“…Several studies have been conducted on the thrust control ability of liquid rocket engines, most of which targeted hydrogen-fueled engines and bipropellant engines. [17][18][19][20][21] For example, it was found that the throttled operation of a rocket engine can degrade excessive acceleration during launch while reducing the thrust required when landing a reusable vehicle. Boccaletto conducted studies on the throttling operation of methane-fueled engines ranging from 40% to 125% when using the SC cycle and the GG cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Proper fuel and oxidizer atomization is critical for stable combustion in liquid rockets. 55 Maintaining a sufficiently high pressure drop across the injector for satisfactory atomization sets a practical lower limit to the depth of throttling that can be achieved. Specialized injectors are required to maintain combustion stability during deep throttling.…”
Section: G Deep Throttling Hot-flow Testingmentioning
confidence: 99%
“…The shift of the coefficients may cause pump operation to be unstable, where the slope between the flow and head coefficients is positive. 3,11,13) As a result of the shift of the coefficients, pump efficiency will become lower. To keep operation of the pump around its design specific speed, a circulation system is integrated to the pump for the throttled operation.…”
Section: Introductionmentioning
confidence: 99%
“…Throttling has been investigated and several engines were tested in deep and shallow throttled conditions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Throttling is also necessary for the rocket-based-combined-cycle engine (RBCC) to change its operation to the ramjet mode. 15) In the rocket engine, thrust is proportional to the combustion chamber pressure.…”
Section: Introductionmentioning
confidence: 99%